Potensi Antibakteri Minuman Fungsional Tradisional Jawa (Wedang Uwuh) Berdasarkan Variasi Waktu Rebusan - Dewatisari, Whika Febria; Hariyadi, Hariyadi (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2024)
Wedang uwuh is a functional beverage prepared by boiling a combination of spices, namely sappan wood, ginger, nutmeg leaves, cinnamon leaves, cloves, and clove leaves. It is reported to have antioxidant, antibacterial, and immune-enhancing properties due to its active compounds. This traditional beverage shows potential in reducing infections caused by Escherichia coli, highlighting the importance of proper preparation methods. The objective of this study was to evaluate the antibacterial activity of wedang uwuh prepared by different boiling duration (5, 10, 15, and 20 min) to determine the optimal time for maximum effectiveness. Phytochemical changes, as indicated by color alterations, were assessed by a descriptive approach while a disc diffusion method was used as an antibacterial assay to measure the inhibition zone diameter against E. coli. Compounds in each treatment were analyzed using GC-MS. Phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, triterpenoids, and tannins in all variations. Antibacterial testing revealed that boiling for 15 min exhibited the highest activity, with an inhibition zone diameter of 10.43±1.33 mm, reflecting strong antibacterial efficacy. This result significantly differed from the 5 and 10 min treatments. The 5 min boiling treatment demonstrated a smaller inhibition zone with an average diameter of 5.71±1.67 mm, indicating moderate antibacterial activity, but it did not differ significantly from the 10 min treatment. A chemical analysis by GC-MS for the 15 min boiling sample successfully identified 23 compounds, and among these chemicals, hexadecanoic acid was found as the predominant component.